Islamic Education Marketing Management in Increasing Public Interest in Elementary Madrasahs - Alwizra, Alwizra; Vina , Reyvina; Gita , Gita Surti Nst; Budi, Budianto (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2024)
Public satisfaction can be in the form of satisfaction with information services, satisfaction with the adequacy of institutional products according to community needs, and satisfaction with affordable financing. Educational institutions must be able to create public satisfaction through excellent educational marketing management. This study aims to determine how educational marketing management is carried out by Madrasah Ibtidaiyah, so that the public is interested in Madrasah Ibtidaiyah. This study uses a qualitative method with an ethnographic approach. Data sources were taken from several informants through in-depth interviews selected using a purposive sampling technique, the informants consisted of 6 educators and 3 education staff who were involved as New Student Admissions Committee. In addition, the data sources for this study were parents/guardians of Madrasah Ibtidaiyah students. Representatives of parents/guardians numbered 17 people, who were randomly selected from representatives of parents of students in the BP. 2023, 2022, and 2021. The key informant in this study was the principal of the Madrasah Ibtidaiyah. All observations and interviews were then analyzed thematically using NVivo 10 qualitative analysis software. The analysis results showed that the educational marketing management implemented by the Madrasah Ibtidaiyah was carried out by approaching the community through activities; i) demonstration of the results of the madrasah program, ii) involving Talu community leaders, iii) parenting programs iv) door-to-door marketing, v) and socialization of student achievements. The demonstration of the results of the madrasah program was carried out through the Ramadhan safari program which was held for a full month of Ramadhan in several mosques/mushallas. Furthermore, through the opening ceremony of several institutions/agencies. Community leaders were carried out through short videos of statements of support and recognition of several Talu community leaders for the Madrasah Ibtidaiyah. The short videos were distributed on several social media. In addition, statements from Talu community leaders were also written in the PPDB brochure by displaying personal data and photos of Talu community leaders. The parenting program is conducted through regular meetings with parents/guardians of students, focusing on developing parents to become effective educators. Door-to-door marketing is a socialization activity carried out by the PPDB Committee to provide information directly to parents/guardians of prospective new students.